Dual-band 3.5/28GHz ellipse patch antenna with L-inverted Slot for 5G applications - Mohamed, Nur Fatin Hannani; Mohamad, Sarah Yasmin; Rahimi, Aiman Hakimi; Ismail, Ahmad Fadzil; Badron, Khairayu; Ahmad, Yasser Asrul; Basri, Atikah Balqis (IEEE, 2026)
Wireless technology has become a medium for information transfer, driven by the continuous evolution of mobile network generations. The fifth generation (5G) mobile network was first implemented in Malaysia in December 2021. Before, the widely used 4G network operated within the 700 MHz, 2.3 GHz, and 2.6 GHz spectrum bands. However, these low- and mid- frequency bands are not fully compatible with the stringent requirements of 5G, which targets ultra-low latency of 1 millisecond, which can be achieved with high-band spectrum. Microstrip patch antennas are considered a promising solution for 5G networks due to their low profile, compact design, and efficient transmission and reception of electromagnetic waves. Moreover, dual-band characteristics can be readily incorporated into patch antenna designs. This paper presents the design and simulation of a dual-band ellipse microstrip patch antenna with L-inverted slot operating at 3.5 GHz (mid-band) and 28 GHz (high-band) for 5G applications. The inclusion of the slot enables dual-band operation, achieving good return loss values of –21.15 dB at 3.5 GHz and –17.91 dB at 28 GHz. The antenna also demonstrates gains of 4.916 dBi and 6.140 dBi at 3.5 GHz and 28 GHz, respectively. It is shown that the design fulfills the baseline criteria for 5G applications, highlighting its promise as a viable option for future wireless communication technology.